Innovation and communication media in virtual teams: An experimental study - Nicola Grözinger; Bernd Irlenbusch; Katharina Laske; Marina Schröder (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
In a novel real-effort setting, we experimentally study the effects of different communication media on creative performance in a collaborative tasks. We find that creative performance significantly decreases when group members communicate via chat instead of face-to-face. However, we find no significant difference between performances of groups that communicate via video conferences as compared to face-to-face. Thus, we provide evidence that barriers to creativity in virtual teams can be mitigated by real-time video conference communication.
Keywords: C91; J30; M52; O30; 330; Creativity; Communication; Laboratory Experiment; Real-effort; Complex Problem Solving; Innovation